How Trust Mediates the Effect of Interactivity, Attractiveness, and Engagement on E-Loyalty - Rahmawida; Rose Rahmidani (Indonesian Journal of Advanced Research, 2026)
This study aims to analyze the influence of platform interactivity, physical attractiveness, and customer engagement on e-loyalty through trust as a mediating variable. The study population consists of Glad2Glow customers who make purchases via TikTok live streaming. The sampling technique used was purposive sampling with 145 respondents. Primary data was collected via a questionnaire and analyzed using Smart PLS. The results indicate that platform interactivity and customer engagement have a significant effect on trust, while physical attractiveness does not have a significant effect. Furthermore, platform interactivity and trust significantly influence e-loyalty, while physical attractiveness and customer engagement do not have a significant influence. Additionally, trust was found to significantly mediate the influence of platform interactivity and customer engagement on e-loyalty, whereas the mediation effect for physical attractiveness was not significant; these findings reinforce the role of trust as a key mechanism in fostering customer loyalty.